INDIGENOUS RHIZOBACTERIA SCREENING FROM TOMATO TO CONTROL RALSTONIA SYZIGII SUBSP. INDONESIENSIS AND PROMOTE PLANT GROWTH RATE AND YIELD - Yanti, Yulmira; Hamid, Hasmiandy; Reflin, Reflin (Universitas Lampung, 2018)
Indigenous rhizobacteria screening from tomato to control Ralstonia syzigii subsp. indonesiensis and promote plant growth rate and yield. Bacterial wilt is the most damaging vascular pathogen on tomato and many other crops in tropical, subtropical and warm temperate areas of the world which limits the production. Rhizobacteria have been concerned as potential biological control agents due to their ability to promote plant growth and health, and their role as antagonists of plant pathogens. The purpose of this research was to screen the best indigenous rhizobacteria (IRB) that able to control bacterial wilt disease and increase growth rate and yield of tomato plant. This research was conducted in 3 stages: (1) Isolation and selection of indigenous rhizobacteria as PGPR on tomato seedlings, consisted of 27 IRB isolates and a control, with triplications; (2) Selection of IRB isolates that control R. syzigii subsp. indonesiensis on tomato plants, which consisted of 8 treatments including 7 IRB and a control with 5 replications; (3) Characterization of IRB isolates ability to promote plant growth (indicated with IAA production & phosphate solubilizing). The variables observed were disease development, growth enhancement and IRB isolate ability to produce IAA and solubilize phosphate. The results showed that all IRB isolates were able to control bacterial wilt disease and increase the growth rate and yield of tomato. IR2.3.5, IR1.3.4 and IR1.4.2 were the best isolates in controlling R. syzigii subsp. indonesiensis and increasing the growth rate and yield by 81.25% and 68.72% respectively. All isolates showed various abilities to produce IAA, however, only isolates IR2.3.5 and IR1.3.4 that had abilities to solubilize phosphate.